Optical coherence tomography findings of the peripheral retina in patients with congenital X-linked retinoschisis - Ayaka Nakajima; Ayaka Nakajima; Kazuki Kuniyoshi; Chiharu Iwahashi; Fukutaro Mano; Takaaki Hayashi; Hiroyuki Kondo; Kei Mizobuchi; Itsuka Matsushita; Akiko Suga; Kazutoshi Yoshitake; Kazutoshi Yoshitake; et al. (Frontiers in Medicine, 2023)
IntroductionCongenital X-linked retinoschisis (XLRS) presents as macular retinoschisis/degeneration in almost all patients and as peripheral retinoschisis in half the patients. Although the optical coherence tomography (OCT) findings of macular retinoschisis have been well investigated, those of peripheral retinoschisis have rarely been reported. This study aimed to report the ultra-widefield OCT findings of the peripheral retina in patients with XLRS.MethodsMedical records of 10 Japanese patients (19 eyes) with clinically and/or genetically diagnosed XLRS were retrospectively reviewed. Funduscopic, electroretinographic, and OCT findings were reviewed and evaluated. Some were also genetically evaluated for the RS1 gene.ResultsOCT of the macula revealed schises and/or cystoid changes in the inner nuclear layer (INL) and outer nuclear layer. In contrast, OCT of the peripheral retina revealed schises and/or cystoid changes in the INL in eight eyes (44%), and/or splitting in the ganglion cell layer (GCL) in 10 (56%) of the 18 eyes with clear OCT images. No schisis or cystoid changes were found in the peripheral OCT images of eight eyes (44%). A 16-year-old boy presented with retinal splitting of the GCL and INL of the inferior retina, although he had no ophthalmoscopic peripheral retinoschisis. Genetic examinations were performed on three patients, all of whom had reported missense mutations in the RS1 gene.ConclusionIn XLRS, peripheral bullous retinoschisis results from GCL splitting in the retina. One of the 10 patients with XLRS showed intraretinal retinoschisis in the GCL in the inferior periphery, which was unremarkable on ophthalmoscopy (occult retinoschisis). Although both peripheral bullous retinoschisis and occult retinoschisis showed splitting/cystic changes in the GCL, further studies are needed to determine whether occult retinoschisis progresses to bullous retinoschisis.